Habitat suitability analysis for sea cucumber mariculture development in the coastal waters of Bangladesh - Muhammad Mizanur Rahman; Subrata Sarker; Md. Rashed Talukder; Md. Shahadat Hossain; Md. Al Mamun; Tanjida Sultana (International Journal of Remote Sensing, 2026)

Evaluating water supply and demand growth in the Gulf Cooperation Council countries: projections and policy implications for sustainable water resources management - Amjad Aliewi; Muhammad Al Rashed; Dalal Sadeqi; Harish Bhandary; Ahmed Sefelnasr; Mohsen Sherif; Ahmed Murad; Dalal Alshamsi; Abdel Azim Ebraheem (Arabian Journal of Geosciences, 2025)

Leveraging machine learning to model salinity and water flux for improved insights into forward osmosis membrane bioreactors - Ali Aldrees; Bilal Siddiq; Wael S. Al-Rashed; Muhammad Faisal Javed; Majid Khan (Journal of Water Process Engineering, 2024)

Novel concept for water scarcity quantification considering nonconventional and virtual water resources in arid countries: Application in Gulf Cooperation Council countries - Muhammad Al Rashed; Ahmed Sefelnasr; Mohsen Sherif; Ahmed Murad; Dalal Alshamsi; Amjad Aliewi; Abdel Azim Ebraheem (Science of The Total Environment, 2023)

Functionalized multi-walled carbon nanotubes for oil spill cleanup from water - Thamer Adnan Abdullah; Tatjana Juzsakova; Sanaa A. Hafad; Rashed Taleb Rasheed; Noor Al-Jammal; Muhammad Ali Mallah; Ali Dawood Salman; P. C. Le; Endre Domokos; Mustafa Aldulaimi (Clean Technologies and Environmental Policy, 2022)
The growing global economy resulted in an incessant increase in transportation and exploitation of oil. Hence, the oil spillage has been considered a serious threat to aquatic and terrestrial ecosystems. Therefore, water purification has been considered a major challenge around the world. There are numerous classical methods available for oil removal from water, but owing to multiple defects and disadvantages, research efforts have focused to find such adsorbents which can improve oil adsorption capability. Traditional adsorbent material typically applied in oil removal includes activated carbon, organoclays, wool, zeolites, etc. These materials suffer from several drawbacks such as low absorption capacity, non-selective absorption, and complicated reusability, whereas nano-adsorbents offer multiple advantages such as having multiple sorption sites, large surface area, short intra-particle diffusion distance, tuneable pore size, and ease of low-temperature modification. Multi-walled carbon nanotubes (MWCNTs) are extensively used adsorbent materials with a strong affinity for the removal of organic pollutants. The functionalization MWCNTs further increase the sorption capacity of adsorbents manifolds to remove organic materials. These nanocomposites are also compatible with green materials and considered environmentally friendly adsorbents. This review paper aims at providing an insight to understand the properties of the MWCNTs and their potential use to adsorb hydrocarbons from water. Moreover, the synthesis methods of those materials, their modification procedures including the functionalization with metal oxide nanoparticles, and applications are also discussed in detail. Graphic abstract

Rutin inhibits carfilzomib-induced oxidative stress and inflammation via the NOS-mediated NF-κB signaling pathway - Naif O. Al-Harbi; Faisal Imam; Mohammed M. Al-Harbi; Othman A. Al-Shabanah; Moureq Rashed Alotaibi; Homood M. As Sobeai; Muhammad Afzal; Imran Kazmi; Ammar Cherkess Al Rikabi (Inflammopharmacology, 2019)

Water Resources in the GCC Countries: An Overview - Muhammad F. Al-Rashed; Mohsen M. Sherif (Water Resources Management, 2000)